2015
DOI: 10.1016/j.gaitpost.2014.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Older adults who have previously fallen due to a trip walk differently than those who have fallen due to a slip

Abstract: Studying the relationships between centre of mass (COM) and centre of pressure (COP) during walking has been shown to be useful in determining movement stability. The aim of the current study was to compare COM-COP separation measures during walking between groups of older adults with no history of falling, and a history of falling due to tripping or slipping. Any differences between individuals who have fallen due to a slip and those who have fallen due to a trip in measures of dynamic balance could potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…The mean walking speed (1.18±0.14 m/s), stride time (1.06±0.08 s) and stride length (1.25±0.08 m) are comparable to those reported by Hollman and colleagues 28 for women of similar age (1.16±0.20 m/s; 1.06±0.13 s; 1.23±0.17 m). These results are also similar to the group that experienced a previous fall due to tripping (1.19±0.20 m/s; 1.06±0.08 s; 1.26±0.17 m) 22 . The findings of Wright and colleagues 22 showed no differences in gait kinematics when non-fallers were compared to individuals with a fall history, irrespective of the cause of the event (i.e., trip or slip).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The mean walking speed (1.18±0.14 m/s), stride time (1.06±0.08 s) and stride length (1.25±0.08 m) are comparable to those reported by Hollman and colleagues 28 for women of similar age (1.16±0.20 m/s; 1.06±0.13 s; 1.23±0.17 m). These results are also similar to the group that experienced a previous fall due to tripping (1.19±0.20 m/s; 1.06±0.08 s; 1.26±0.17 m) 22 . The findings of Wright and colleagues 22 showed no differences in gait kinematics when non-fallers were compared to individuals with a fall history, irrespective of the cause of the event (i.e., trip or slip).…”
Section: Discussionsupporting
confidence: 86%
“…There are several indications that these populations differ with respect to their ability to recover from a trip 21 , in which older adults are less able to regain balance and, therefore, more vulnerable to falls 20 . Although Wright and colleagues 22 showed that previous experience of falling did not result in gait pattern changes, others have reported a more cautious pattern due to fear of tripping and falling 23 , which may occur within and between sessions. Older adults tend to be more susceptible to fear of falling than their young counterparts 23 .…”
Section: Introductionmentioning
confidence: 98%
“…All phases of the gait cycle, including stance and swing, plus inter limb coordination appear to be influenced by the length, velocity and stretch sensitivity of spindle afferents, Since defects in this process may explain the presence of a heightened fall risk in individual's with neuromuscular deficiencies and others [66,67] , as well as why walking trajectories of fallers who have tripped are more extensive than those who have slipped [68] , this paper examined what we know about muscle spindle activity in the context of locomotion for purposes of advancing our understanding of the nature of falls injuries among older adults and others. Although the current hypothesis has not been put to any adequate test, the available data do imply that an improved understanding of the link between muscle afferents, and their behavior as this affects locomotor activity can potentially help to predict who is at risk, and explain why exercise can reduce falls injuries in some cases, but not others.…”
Section: Resultsmentioning
confidence: 99%
“…After repeating this for a minimum of 20 walking trials, six of the participants were unexpectedly slipped, while the other six were unexpectedly tripped, during a randomly selected trial. Each participant was slipped or tripped only once because previous research has shown that gait characteristics are altered following exposure to a slip or a trip [2628]. Exposing a participant to both a slip or trip would significantly influence gait characteristics, and likely head acceleration, for the second perturbation.…”
Section: Methodsmentioning
confidence: 99%